2020
DOI: 10.1101/2020.08.28.20183848
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social Determinants Associated with COVID-19 Mortality in the United States

Abstract: This study examines social determinants associated with disparities in COVID-19 mortality rates in the United States. Using county-level data, 42 negative binomial mixed models were used to evaluate the impact of social determinants on COVID-19 outcome. First, to identify proper controls, the effect of 24 high-risk factors on COVID-19 mortality rate was quantified. Then, the high-risk terms found to be significant were controlled for in an association study between 41 social determinants and COVID-19 mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…*** Disparities in COVID-19 hospitalization by race and ethnicity varied by U.S. Census region and became less pronounced over the course of the pandemic as the proportion of White patients hospitalized with COVID-19 increased. Identification of the specific social determinants of health (e.g., access to health care, occupation and job conditions, housing instability, and transportation challenges) that contribute to geographic *** https://www.cdc.gov/coronavirus/2019-ncov/community/health-equity/ racial-ethnic-disparities/disparities-illness.html and temporal differences in racial and ethnic disparities in COVID-19 infection and poor health outcomes is critical (6,7,9,10). A better understanding of these factors at a local level can help guide tailored public health prevention strategies and equitable allocation of resources, including COVID-19 vaccination, to better address COVID-19-related health disparities and can inform approaches to achieve greater health equity during future public health threats.…”
Section: Discussionmentioning
confidence: 99%
“…*** Disparities in COVID-19 hospitalization by race and ethnicity varied by U.S. Census region and became less pronounced over the course of the pandemic as the proportion of White patients hospitalized with COVID-19 increased. Identification of the specific social determinants of health (e.g., access to health care, occupation and job conditions, housing instability, and transportation challenges) that contribute to geographic *** https://www.cdc.gov/coronavirus/2019-ncov/community/health-equity/ racial-ethnic-disparities/disparities-illness.html and temporal differences in racial and ethnic disparities in COVID-19 infection and poor health outcomes is critical (6,7,9,10). A better understanding of these factors at a local level can help guide tailored public health prevention strategies and equitable allocation of resources, including COVID-19 vaccination, to better address COVID-19-related health disparities and can inform approaches to achieve greater health equity during future public health threats.…”
Section: Discussionmentioning
confidence: 99%
“…But, according to recent reports (85), a lot of work is needed to support large-scale dissemination and implementation through a multisectoral approach that has the capacity to respond to social needs, mobilize community social capital (8,86), and provide training to social and health care providers on substance use and mental health disorders (8). These approaches can reduce health, economic and social inequity (87) that exacerbate mental illness (7) and alcohol consumption (88).…”
Section: Discussionmentioning
confidence: 99%
“…27,28 By leveraging large, national datasets, it is possible to explore many of the SDoH that influence COVID-19. A recent study by Debopadhaya et al 29 explored the association of various social determinants with COVID-19 mortality at the county level across the entire USA. They found that high rates of lacking insurance, limited English proficiency, air pollution, overcrowded housing, and lower educational attainment were all associated with increased COVID-19 mortality.…”
Section: Section 3: Social Determinants Of Covid-19mentioning
confidence: 99%